Comprehensive nuclear materials. - Konings, Rudy J. M.; Allen, Todd R.; Stoller, Roger E.; Yamanaka, Shinsuke (Elsevier, 2012)
Comprehensive Nuclear Materials discusses the major classes of materials suitable for usage in nuclear fission, fusion reactors and high power accelerators, and for diverse functions in fuels, cladding, moderator and control materials, structural, functional, and waste materials. The work addresses the full panorama of contemporary international research in nuclear materials, from Actinides to Zirconium alloys, from the worlds' leading scientists and engineers. Critically reviews the major classes and functions of materials, supporting the selection, assessment, v.